Motorcycle parking building layout design at Nusa Putra University - Fauziah Syifa; Agung Abdullah Anugrah; Gomes Tarisa; Damas Permadi Dio; Sukmayu Saputri Utamy; Hidayat Muhammad (BIO Web of Conferences)
The increase in educational activities and infrastructure at universities often leads to a rise in vehicle volume on campuses in Indonesia. This study aims to gather information on the characteristics and parking space needs at Nusa Putra University, predict parking space needs for the next 5 years, and determine effective parking building layout designs at Nusa Putra University. Data collection involves direct field observation through parking space inventory surveys and cordoning parking surveys. The collected data is analyzed using statistical forecasting with the least square method and comparative value statistics. The results show that the current capacity of 254 parking space unit (PSU) for two-wheelers cannot meet the demand of 539 PSU. Additionally, there are two proposed layout and location plans for a parking building to meet Nusa Putra University's predicted 2028 needs of 1059 PSU: Plan A (south of the auditorium) with a 7-story building accommodating 1076 PSU, and Plan B (east of Building B) with a 4-story building accommodating 1012 PSU.